Concepts of Experiential Learning in Digital Collaboration: New Perspectives for the Higher Education Sector - Knoblauch, Christoph (International Journal of Advanced Corporate Learning (iJAC), 2023)
Reflecting on the manifold interrelations of experience and education, this paper focuses on concepts of experiential learning in digital collaboration in the higher education sector. Therefore, evaluation findings from a digital project-based course in the higher education sector are discussed with a primary focus on students’ experiences in collaborative digital settings. It thereby discusses the results of a qualitative study that concentrates on the students’ experiences within the course and the collaborative projects. The study uses digital qualitative interviews for the evaluation research. By doing so, the study investigates and reflects the quality of students’ experiences and their possible influences on learning. It also discusses the question of how these experiences can be constructively implemented to improve future digital or blended-learning scenarios in the higher education sector. On that basis, possible implications for concepts of experiential learning in digital collaboration are discussed.